The role of sexist discrimination in adult women's identity development - Anthis, Kristine (Sex Roles, 2002)
The purpose of the current study was to examine the relationship between sexist discrimination and identity development in a sample of adult women. Participants completed a scale to indicate the extent to which sexist events had occurred in their lives and a measure of identity at 2 different data collection periods that spanned approximately 5 months. The results indicated that sexist events reported to occur within the last year at the first data collection period significantly predicted identity scores at the second data collection period. These findings are discussed in terms of how sexist discrimination may play a role in adult women's identity development and in terms of the additional psychometric data that supports the validity of the measure of sexist discrimination.
Keywords: dept.psy; identity; sexist discrimination; women